Pathways of development in the hillsides of Honduras: causes and implications for agricultural production, poverty, and sustainable resource use - Pender, John L.; Scherr, Sara J.; Durón, Guadalupe (International Food Policy Research Institute, 1999)
Based on a survey of 48 communities in central Honduras, this paper identifies the major pathways of development that have been occurring in central Honduras since the mid-1970s, their causes and implications for agricultural productivity, natural resource sustainability, and poverty. Six pathways of development were identified: 1) basic grains expansion communities-where basic grains production is the dominant activity and increased basic grains production has occurred; 2) basic grains stagnation communities-where basic grains production is dominant but has stagnated or declined; 3) coffee expansion communities-where coffee production is important and has been increasing in importance; 4) horticultural expansion communities-where substantial adoption and expansion of horticultural crops has occurred; 5) forestry specialization communities-where forestry activities are important and basic grains production is stagnant or declining; and 6) nonfarm employment communities-where nonfarm employment is a major and increasing source of income. The findings imply that a “one-size-fits-all” approach to technical assistance is unlikely to be successful, since different approaches show promise in different pathways.